Corrosion performance of melt-spun Mg67Zn28Ca5 metallic glass in artificial sweat - Wang, Yongsheng (2013)
The Mg-based metallic glass developed in this study provides an alternative for Mg alloys for being used in daily life. In this study, the corrosion behaviors of melt-spun MgZnCa ribbons with and without heat treatment were investigated in artificial sweat. Surface morphology analysis showed that amorphous ribbon was more sensitive to suffer from pitting corrosion. Electrochemical testing and measurement of metal ion concentrations indicate that ribbons in amorphous structure were nobler with smaller corrosion current and possessed much slower dissolution rate of metal ions. A Zn-rich passivation layer is detected on the surface of amorphous ribbon, indicating that Zn is more effective in amorphous ribbon to protect the inner active metal.